Isolamento e caracterização de microrganismos em leite cru refrigerado e leite UHT no estado de Goiás e desenvolvimento de filme ativo antimicrobiano para inibição de Bacillus sporothermodurans - PEREIRA, Flavio Evans Vilela (2010)
Raw milk is a natural culture medium for the microbial growth and easy deterioration, because of that, thermal processing is needed as soon as possible. A new technology has been used to improve the food quality, active packaging, such as antimicrobial films, wich the intention to control the microbial growth in the products. The aim of this study was to evaluate the UHT milk quality produced in Goiás State, isolation and identification of Bacillus sporothermodurans, beside create a antimicrobial film for inhibition of this microrganism high heat resistance spore former. The isolation of psychrotrophic in raw milk was used PCA with incubation at 21 °C for 72h. To evaluate the UHT milk has been doing research on aerobic mesophilic in PCA with incubation at 30 °C for 72h and to thermoresistents microrganisms was in ABHI with incubation at 35 °C for 48h. The identification of isolates was performed according to convetional methods of biochemistry identification. From raw milk, the psychrotrophic microrganisms most isolates were Staphylococcus sp. and Corynebacterium sp., both with 21,5% from 70 isolates, verifying a higher contauge of Gram-positive microrganisms (82,85%). Considering the 157 UHT isolates, just 31 were identified as Gram-positive microrganisms through biochemical tests, only 2 correponded to B. sporothermodurans, although there are differences from the tests and their results between various authors, requiring more accurate identification using molecular biology. The antimicrobial film maded of cellulose acetate with addition of nisin to inhibit the development of B. sporothermodurans, the results indicated action of nisin in inhibition this microrganism, however, when incorporated into the film, did not show the expected results in both tests, solid and liquid medium, although the specific rate (μ) growth of the microrganism was changing iin the lowest concentration tested. There is a need to conduct testing in foods, mainly in dairy products which have been reported contamination by B. sporothermodurans.